APPROACHES, MODELS AND TOOLS OF CORPORATE GOVERNANCE IN CONDITIONS OF WAR AND ECONOMIC TURBULENCE - DYKHA, Mariia; DYKHA, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article describes the turbulent conditions of the functioning of joint-stock companies (high level of uncertainty about the future development of events; economic instability; frequent and unpredictable shocks caused by war; complication of the process of making strategic decisions, etc.). It is substantiated that the implementation of corporate governance in modern conditions is accompanied by challenges and risks, in particular, such as disruption of communication between management and owners; increased internal corruption vulnerability due to weaker control over financial flows; decreased confidence of investors and creditors, withdrawal of some foreign investors; the need to adapt to new regulatory norms of wartime; increased dependence on state support, grants, etc. Challenges and risks necessitate changes in the models of functioning of corporate structures and in their management. The strengthening of the role of the state as a regulator and as a shareholder is analyzed, in particular, through nationalization, forced alienation of shares of companies (in particular, PJSC Ukrtatnafta, JSC Motor Sich, PrJSC AvtoKrAZ and PrJSC Zaporizhtransformator), important for the functioning of Ukraine in conditions of war and ensuring its defense. The identification of signs and characteristics of turbulence in the economy, risks and transformations of corporate governance in Ukraine, proposals for state institutions, investors and company management has theoretical and practical significance. It is substantiated that in a turbulent environment it is advisable to implement adaptive models and tools of anti-crisis strategy; flexible models of supervisory boards, investor participation; new tools of communication and trust, which in general will contribute to increasing the efficiency of corporate governance and ensuring the stable functioning of joint-stock companies.